Effect of intra-patient variability on personalized parameters of glucose-insulin dynamic models for exercise, meal, and insulin interventions - NAVIYN PRABHU BALAKRISHNAN (Elsevier BV, 2021)
IFAC Proceedings Volumes (IFAC-PapersOnline)